Digital Signature Approach for Image Authentication - Bausys, R.; Kriukovas, A. (Elektronika ir Elektrotechnika, 2008)
The paper examines watermarking and digital signature based approaches for image authentication. It is shown that digital signature has a better performance at least in semi-blind watermarking case. Digital signature based method for image authentication and pixelwise tamper localization is proposed. The method is able to restore tampered pixels to initial value. Ill. 5, bibl. 10 (In English; summaries in English, Russian and Lithuanian).